2019
DOI: 10.1259/bjr.20190663
|View full text |Cite
|
Sign up to set email alerts
|

Can mammogram readers swiftly and effectively learn to interpret first post-contrast acquisition subtracted (FAST) MRI, a type of abbreviated breast MRI?: a single centre data-interpretation study

Abstract: Objectives: To assess whether NHS breast screening programme (NHSBSP) mammogram readers could effectively interpret first post-contrast acquisition subtracted (FAST) MRI, for intended use in screening for breast cancer. Methods: Eight NHSBSP mammogram readers from a single centre (four who also read breast MRI (Group 1) and four who do not (Group 2)) were given structured FAST MRI reader training (median 4 h: 32 min). They then prospectively interpreted 125 FAST MRIs (250 breasts: 194 normal and 56 cancer) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 23 publications
(26 reference statements)
0
42
0
Order By: Relevance
“…This is to improve the specificity, including information that allows greater discrimination between benign and malignant lesions and make it possible to evaluate the tumor uptake. Other studies explicitly incorporate the use of maximum intensity projection (MIP) images of post-contrast examinations as part of the reading protocol [19] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] . This derivated image highlights maximum enhancement areas such as tumor or lymph nodes, and allows for the assessment of the relationship among arteries, veins, and blood vessels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is to improve the specificity, including information that allows greater discrimination between benign and malignant lesions and make it possible to evaluate the tumor uptake. Other studies explicitly incorporate the use of maximum intensity projection (MIP) images of post-contrast examinations as part of the reading protocol [19] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] . This derivated image highlights maximum enhancement areas such as tumor or lymph nodes, and allows for the assessment of the relationship among arteries, veins, and blood vessels.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, from the subset of 10 articles that studied subjects prospectively enrolled: 4 studied feasibility of ABB-AP for screening patients at high-risk of breast cancer [50] , [65] , [56] , [62] ; two analyzed studies of women who carried a mildly or moderately increased risk, either because of dense breast tissue, mild or moderate family history, or personal history of breast cancer [19] , [63] ; and two more, women with a personal history of breast cancer [52] , [66] . Another one, studied asymptomatic women with a negative mammogram, which did not have a personal history of breast cancer or prior chest radiation therapy [40] .…”
Section: Resultsmentioning
confidence: 99%
“…Published studies of abMRI techniques have used expert MRI readers for interpretation, and this has been suggested as a potential barrier to expansion of the technique for personalised screening with abMRI 24 . However, with a single day's standardised training 33 to interpret the simplest of the abMRI techniques (FAST MRI), an early study suggests that professionals who are already competent at reading mammograms can achieve similar levels of accuracy of interpretation of abMRI to that of expert breast MRI readers 34 . If these results should be validated in subsequent studies 35 , limitation to expansion of the role of abMRI (FAST protocol) on the grounds of workforce feasibility will have been reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, it has recently been suggested that radiologists who are already competent at reading mammograms can achieve similar levels of accuracy of interpretation of the abbreviated MRI protocol proposed by Kuhl C.K. et al (consisting of first postcontrast subtracted images and maximum-intensity projection only) [ 17 ] to that of expert breast MRI readers [ 18 ].…”
Section: Introductionmentioning
confidence: 99%